Transdisciplinary care in the emergency department: A qualitative analysis. (March 2016) - Innes, Kelli; Crawford, Kimberley; Jones, Tamsin; Blight, Renee; Trenham, Catherine; Williams, Allison; Griffiths, D.; Morphet, Julia
Highlights: The transdisciplinary team consists of nurses and allied health staff. Staff in the transdisciplinary team autonomously assess and manage diverse patient presentations. The transdisciplinary team is a novel approach to expedite ED patient flow. ED staff, patients and carers favoured the transdisciplinary care model. Abstract: In response to increasing demands some emergency departments have introduced transdisciplinary care coordination teams. Such teams comprise staff from multiple disciplines who are trained to perform roles outside their usual scope of practice. This study aimed to critically evaluate the patient, carer and ED staff perceptions of the transdisciplinary model of care in an emergency department in a Melbourne metropolitan hospital. The evaluation of the transdisciplinary team involved interviews with patients and carers who have received the transdisciplinary team services, and focus groups with emergency nursing and transdisciplinary team staff. Analysis of the data revealed that the transdisciplinary model provided an essential service, where staff members were capable of delivering care across all disciplines. The ability to perform comprehensive patient assessments ensured safe discharge, with follow-up services in place. The existence of this team was seen to free up time for the emergency nursing staff, enabling them to see other patients, and improving department efficiency while providing quality care and increasing staff satisfaction. This study identified several important factors which contributed to the success of the transdisciplinary team, which was well integrated into the larger emergency department team.